2020
DOI: 10.3329/ajmbr.v6i3.49803
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of antibiotics and antibiotic usage behavior among the people of Dhaka, Bangladesh

Abstract: Bangladesh is a developing country with a very high prevalence of antibiotic resistance where irrational use of antibiotics is very common. This cross-sectional survey was conducted to assess the knowledge of antibiotics and antibiotic usage behavior (Antibiotic use, self-medication, adherence to therapy) among the people of Bangladesh. The association between participants’ knowledge of antibiotics and their antibiotic usage behavior was also analyzed. A cross-sectional survey based on a structured questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…The findings were also similar to another study in Bangladesh. 7 Regarding age of the dental patients, mean (±SD) age of the respondents were 41.11(±14.09) years which coincide with other studies. 11,13 In this study, regarding antibiotic consumption behaviour of the dental patients, 35.9%, 32.8% and 31.3% patients showed good, average and poor behaviour respectively.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The findings were also similar to another study in Bangladesh. 7 Regarding age of the dental patients, mean (±SD) age of the respondents were 41.11(±14.09) years which coincide with other studies. 11,13 In this study, regarding antibiotic consumption behaviour of the dental patients, 35.9%, 32.8% and 31.3% patients showed good, average and poor behaviour respectively.…”
Section: Discussionsupporting
confidence: 88%
“…Here, both antibiotic abuse and antibiotic misunderstandings are highly frequent. 7 Despite the substantial research into the behavior of self-medication and irrational antibiotic consumption, there is little information concerning its mode among dental patients in underdeveloped nations. According to the findings of a study, in a tertiary dental hospital in Bangladesh, 80% of respondents stopped their scheduled dosage after they became well.…”
Section: Research Papermentioning
confidence: 99%
“…In a 2022 survey on rural Bangladeshi people, respondents were found to have moderate knowledge but an aversive attitude toward proper antibiotic use [ 9 ]. In a cross-sectional survey conducted in Bangladesh, most respondents (83.2%) were unaware that antibiotic use is inappropriate for most common colds [ 10 ]. A recent review has demonstrated that the availability of antibiotics without prescriptions significantly contributes to AMR in Bangladesh [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Bangladesh, the antibiotic resistance was only familiar to 56.1% of population, while 20.5% was self-administrated. 10 There may be a lack of awareness and concerns regarding the harmful consequences of antibiotic self-administering and associated complications such as antibiotic resistance. Even though the government prohibits antibiotic without prescription, due to the lack of enforcement of anti-antibiotic legislation, non-prescription antibiotic use is rampant.…”
Section: Introductionmentioning
confidence: 99%
“…The issues surrounding self-medication with antibiotics are exacerbated in the developing world because they are combined with other problems such as poverty, lack of access to medications and knowledge about prescription medications, poor quality of health care facilities, and ineffective enforcement of medicine-related legislation. [9][10][11] According to a previous survey conducted in Italy, merely 9.8% of the general population recognized antibiotic, while 21.3% comprehended how to use them efficiently. 8 Antibiotic resistance, however, has emerged as a global problem as the use of antibiotic among citizens has increased substantially.…”
Section: Introductionmentioning
confidence: 99%